Bariatric surgery prior to total knee arthroplasty is not associated with lower risk of revision: a register-based study of 441 patients - Ighani Arani, Perna; Wretenberg, Per; Ottosson, Johan; Robertsson, Otto; W-Dahl, Annette (Acta Orthopaedica, 2020)
Background and purpose — Obesity is a considerable medical challenge in society. We investigated the risk of revision for any reasons and for infection in patients having total knee arthroplasty (TKA) for osteoarthritis (OA) within 2 years after bariatric surgery (BS) and compared them with TKAs without BS. Patients and methods — We used the Scandinavian Obesity Surgery Registry (SOReg) and the Swedish Knee Arthroplasty Register (SKAR) to identify patients operated on in 2009–2019 with BS who had had primary TKA for OA within 2 years after the BS (BS group) and compared them with TKAs without prior BS (noBS group). We determined adjusted hazard ratio (HR) for the BS group and noBS group using Cox proportional hazard regression for revision due to any reasons and for infection. Adjustments were made for sex, age groups, and BMI categories preoperatively. Results — 441 patients were included in the BS group. The risk of revision for infection was higher for the BS group with HR 2.2 (95% CI 1.1–4.7) adjusting for BMI before the TKA, while the risk of revision for any reasons was not statistically significant different for the BS group with HR 1.3 (CI 0.9–2.1). Corresponding figures when adjusting for BMI before the BS were HR 0.9 (CI 0.4–2) and HR 1.2 (CI 0.7–2). Interpretation — Our findings did not indicate that BS prior to TKA was associated with lower risk of revision.